High-strength corrosion-resistant marine aluminum alloy plate and processing technology thereof

By applying functional coating on the aluminum alloy substrate and performing deep cold treatment, the corrosion and impact problems of marine aluminum alloy in the marine environment are solved, significantly improving its corrosion and impact resistance and extending its service life.

CN119307793AActive Publication Date: 2025-01-14GUANGZHOU GOLDEN ALUMINUM ALUMINUM

Patent Information

Application Number
CN202411265461.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-14
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

Marine aluminum alloys are susceptible to electrochemical corrosion and low-speed impact loads in the marine environment, resulting in insufficient corrosion resistance and impact resistance. The single function of traditional coatings is difficult to meet the needs of complex environments.

Method used

The surface of the aluminum alloy substrate is coated with anticorrosion coating and undergoes deep cold treatment. The composite nanomaterial and modification curing agent are added to the coating. The composite nanomaterial is formed by self-assembly of functionalized montmorillonite and carbon nanotubes, and the combined ring is combined. Oxygen resin and flame retardant improve the corrosion resistance, impact resistance and flame retardant properties of aluminum alloys.

Benefits of technology

It significantly improves the overall corrosion resistance and strength of aluminum alloy sheets, effectively prevents acid rain and smoke corrosion, extends service life, and improves impact and flame retardant properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005036996190000121
    Figure BDA0005036996190000121
Patent Text Reader

Abstract

The invention relates to the field of aluminum alloy plates, and discloses a high-strength corrosion-resistant marine aluminum alloy plate and a processing technology thereof.The aluminum alloy plate comprises an aluminum alloy base material and a corrosion-resistant coating, and the aluminum alloy base material is prepared from, by weight, 0.4%-0.8% of Si, 0.5%-0.7% of Fe, 0.15%-0.4% of Cu, 0.1%-0.15% of Mn, 0.8%-1.2% of Mg, 0.04%-0.35% of Cr, 0.1%-0.25% of Zn, 0.05%-0.15% of Ti and the balance Al and inevitable impurities; the anticorrosive coating comprises the following raw materials in parts by weight: 40-65 parts of epoxy resin, 5-15 parts of a composite nano material, 3-7 parts of a modified curing agent, 1-5 parts of a curing agent, 1-3 parts of a wetting agent, 0.5-1 part of a defoaming agent, 0.1-1 part of a flatting agent and 0.1-0.5 part of a dispersing agent; the surface of the prepared aluminum alloy base material is coated with the anti-corrosion coating, the plate is subjected to subzero treatment after casting forming, and the composite nano material and the modified curing agent are added, so that the plate is endowed with excellent impact strength, corrosion resistance and flame retardance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy plates, and in particular relates to a high-strength, corrosion-resistant marine aluminum alloy plate and a processing technology thereof. Background Art

[0002] With the rapid development of the shipbuilding industry, the requirements for lightweight ships are also increasing. Aluminum alloys are widely used in the shipbuilding industry due to their high strength, low density, high fluidity, high filling capacity, good corrosion resistance and low melting point. Marine aluminum alloys must have strong corrosion resistance because they are exposed to mechanical impact, chemical corrosion, electrochemical corrosion and biological corrosion of planktonic microorganisms in seawater in the marine environment for a long time.

[0003] Due to the relatively low corrosion potential of aluminum alloy, it is easily affected by electrochemical corrosion in a humid environment, resulting in the occurrence of electrochemical corrosion. In order to improve the corrosion resistance of aluminum alloy, the use of organic coating to protect aluminum alloy is one of the more economical and effective methods. However, the function of traditional coatings is single and it is difficult to meet the service needs of complex environments. In addition, the impact resistance of aluminum alloy has received widespread attention in recent years. Thin-walled aluminum alloy structures such as the bottom and side of ships may be subjected to low-speed impact loads such as collision, grounding and reef impact during their service life, resulting in irreversible plastic deformation such as impact pits in the ship structure. Summary of the invention

[0004] In order to solve the deficiencies mentioned in the above-mentioned background technology, the purpose of the present invention is to provide a high-strength corrosion-resistant marine aluminum alloy plate and its processing technology. By coating an anti-corrosion coating on the surface of the aluminum alloy substrate after preparation, and then subjecting the plate to deep cold treatment after casting, the overall corrosion resistance and strength of the aluminum alloy plate are significantly improved, and the composite nanomaterials and modified curing agents added to the anti-corrosion coating give the aluminum alloy plate excellent impact strength, corrosion resistance and flame retardant properties.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A high-strength, corrosion-resistant marine aluminum alloy plate comprises an aluminum alloy substrate and an anti-corrosion coating coated on the surface of the aluminum alloy substrate, wherein the aluminum alloy substrate is composed of the following raw materials in weight percentage: Si: 0.4-0.8%, Fe: 0.5-0.7%, Cu: 0.15-0.4%, Mn: 0.1-0.15%, Mg: 0.8-1.2%, Cr: 0.04-0.35%, Zn: 0.1-0.25%, Ti: 0.05-0.15%, and the balance is Al and unavoidable impurities; the anti-corrosion coating comprises the following raw materials in weight parts: 40-65 parts of epoxy resin, 5-15 parts of composite nanomaterials, 3-7 parts of modified curing agent, 1-5 parts of curing agent, 1-3 parts of wetting agent, 0.5-1 part of defoaming agent, 0.1-1 part of leveling agent, and 0.1-0.5 part of dispersant;

[0007] The composite nano material is prepared by functionalizing activated montmorillonite with octadecyltrimethoxysilane and cage-type silsesquioxane, further loading zinc ions through electrostatic adsorption, and then self-assembling with modified carbon nanotubes to form the composite nano material, wherein the activated montmorillonite is prepared by treating with γ-aminopropyltriethoxysilane and succinic anhydride, and the modified carbon nanotubes are prepared by amidation reaction of carboxylated carbon nanotubes with triethylenetetramine and proton acid salt formation reaction; and the modified curing agent is prepared by reacting a flame retardant (2,4-xylyl)phenylphosphine oxide with 1,5-naphthalenediamine and terephthalaldehyde through a chemical reaction.

[0008] Preferably, the curing agent is polyamide; the wetting agent is polydimethylsiloxane; the defoaming agent is one of fatty alcohol polyoxyethylene ether or alkylphenol polyoxyethylene ether; the leveling agent is sodium polyacrylate; and the dispersant is one of BYK-190 or BYK-191.

[0009] Preferably, the method for preparing the composite nanomaterial comprises the following steps:

[0010] (1) N, N-diisopropylcarbodiimide, 1-hydroxybenzotriazole and carboxylated carbon nanotubes are added to N, N-dimethylformamide, and ultrasonically dispersed uniformly. Then, triethylenetetramine is added and stirred for 20 to 24 hours. After the reaction is completed, the product is filtered and washed, and ultrasonically dispersed in deionized water. Hydrochloric acid solution is added dropwise under stirring and stirred for 0.5 to 1 hour to prepare modified carbon nanotubes;

[0011] (2) taking γ-aminopropyltriethoxysilane and succinic anhydride in N,N-dimethylformamide, stirring at 75-90° C. for 2-4 hours to form a mixed solution, ultrasonically dispersing montmorillonite in N,N-dimethylformamide, adding deionized water to mix, and then adding it to the mixed solution and continuing to stir for 3-5 hours. After the reaction is completed, centrifuging, washing, and drying are performed to prepare activated montmorillonite;

[0012] (3) Deionized water, propanol, acetonitrile and tetraethylammonium hydroxide are placed in a reactor, γ-aminopropyltriethoxysilane is added, and the mixture is stirred at 45 to 55° C. for 20 to 24 hours. After the reaction is completed, the mixture is subjected to rotary evaporation, washing and drying to prepare a cage-type silsesquioxane;

[0013] (4) taking activated montmorillonite and dispersing it in anhydrous ethanol by ultrasonic, adding tetraethyl silicate and octadecyltrimethoxysilane, stirring and reacting at 45-60° C. for 8-12 hours, then heating to 170-180° C., adding cage-type silsesquioxane and polyformaldehyde, and continuing to stir and react for 14-16 hours. After the reaction is completed, centrifugation, washing, and drying are performed to prepare functionalized montmorillonite;

[0014] (5) ultrasonically dispersing the functionalized montmorillonite in deionized water, then adding zinc nitrate and stirring the mixture at 55-70° C. for 3-4 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain a modified montmorillonite.

[0015] (6) The modified montmorillonite is ultrasonically dispersed in deionized water, stirred at 75-85° C. for 15-30 min, and then the modified carbon nanotubes are added and stirred for 20-24 h. After the reaction is completed, the composite nanomaterial is prepared by filtering, washing, and drying.

[0016] Preferably, in step (4), the addition ratio of activated montmorillonite, tetraethyl silicate, octadecyltrimethoxysilane and cage-type silsesquioxane is 3 g: 2-3 mL: 1-2 mL: 10-16 g.

[0017] Preferably, in step (5), the mass ratio of the functionalized montmorillonite to zinc nitrate is 1:1.5-2.

[0018] Preferably, in step (6), the mass ratio of the modified montmorillonite to the modified carbon nanotubes is 10-15:1.

[0019] Preferably, the preparation method of the modified curing agent comprises the following steps:

[0020] A. Phenyl phosphorus dichloride is placed in a reactor, m-xylene and anhydrous aluminum chloride are added, the temperature is raised to 70-85° C. for reaction for 8-12 hours, after the reaction is completed, the reaction is cooled to room temperature, hydrochloric acid and benzene are added for hydrolysis, the organic layer is separated, the aqueous layer is extracted with benzene, the organic layers are combined, washed with deionized water, and the organic solvent is evaporated under reduced pressure to prepare (2,4-xylyl)phenyl phosphorus oxide flame retardant;

[0021] B. Take 1,5-naphthalenediamine in a reactor, add ethanol solvent to disperse it evenly, take terephthalaldehyde dissolved in ethanol and add it to the reactor, place it at 50-75°C for reflux reaction for 4-6 hours, then take (2,4-xylyl)phenylphosphine oxide flame retardant dissolved in ethanol and add it to the reactor, heat it to 75-85°C for reaction for 5-7 hours, and after the reaction is completed, filter, wash and dry it to prepare a modified curing agent.

[0022] Preferably, in step A, the mass ratio of phenylphosphonium dichloride, m-xylene and anhydrous aluminum chloride is 1:0.5-0.7:0.5-0.8.

[0023] Preferably, in step B, the mass ratio of 1,5-naphthalenediamine, terephthalaldehyde and (2,4-xylyl)phenylphosphine oxide flame retardant is 2.3-2.7:1:3.4-4.1.

[0024] The processing technology of the high-strength corrosion-resistant marine aluminum alloy plate as described above comprises the following steps:

[0025] S1. Weigh each element according to the weight percentage and put it into a smelting furnace. Set the temperature in the furnace to 750-800°C. After all the materials in the furnace are melted, stir them evenly for 30-45 minutes. After stirring, heat them to 850°C and keep them still for 10-20 minutes. Slag is removed and samples are taken for analysis. The alloy composition is tested and adjusted to obtain alloy materials.

[0026] S2, refining the alloy material, the refining temperature is set to 700-730°C, the refining time is 20-25min, and after refining, it is left to stand for 15-20min, and then cast to obtain a slab, and then heat-treat it at 150-180°C for 4-8h to obtain an aluminum alloy slab;

[0027] S3, hot rolling the aluminum alloy slab, heating it from 180 to 220° C. to 250 to 280° C., then keeping it warm for 5 to 7 hours, and then cold rolling it, with a feed temperature of 300 to 350° C. and a final rolling temperature of 220 to 250° C., cleaning and drying the slab after hot rolling and cold rolling to obtain an aluminum alloy substrate;

[0028] S4, taking parts by weight of epoxy resin, modified curing agent, composite nanomaterial, curing agent, wetting agent, defoaming agent, leveling agent and dispersant into a high-speed disperser for stirring and dispersing, heating to 120-150° C. and evenly dispersing for 30-50 minutes, taking out the obtained anti-corrosion coating, and then evenly coating the anti-corrosion coating on the surface of the aluminum alloy substrate, drying and cooling, to obtain an anti-corrosion aluminum alloy plate;

[0029] S5. Soak the anti-corrosion aluminum alloy plate in hydrogen peroxide in a deep freezer for 10 to 20 minutes. Take it out and keep it at -10°C for 20 to 30 minutes, then keep it at -40°C for 10 to 20 minutes, then keep it at -90°C for 30 to 40 minutes, then take it out of the deep freezer, place it in the air to naturally return to room temperature, and place it for 1 to 2 hours to obtain a high-strength and corrosion-resistant marine aluminum alloy plate.

[0030] Beneficial effects of the present invention:

[0031] The aluminum alloy plate prepared by the present invention has excellent strength, elongation and corrosion resistance, and can effectively meet the application requirements of ships for high-strength and corrosion-resistant aluminum alloy plates. After the preparation, an anti-corrosion coating is coated on the surface of the aluminum alloy substrate. After casting, the plate is subjected to deep cold treatment, which significantly improves the overall corrosion resistance and strength of the aluminum alloy plate, effectively avoids corrosion caused by external factors such as acid rain and smog, and extends the service life of the aluminum alloy plate.

[0032] The invention uses carboxylated carbon nanotubes to undergo amidation reaction with triethylenetetramine and proton acid salt formation reaction to obtain modified carbon nanotubes, and simultaneously uses gamma-aminopropyltriethoxysilane and succinic anhydride to activate the surface of montmorillonite so that the surface of montmorillonite is rich in hydroxyl and carboxyl groups, and then uses octadecyltrimethoxysilane and cage-type silsesquioxane to functionalize the activated montmorillonite, the montmorillonite functionalized with octadecyltrimethoxysilane imparts super-hydrophobicity to the coating, and the cage-type silsesquioxane with amino groups is grafted between the montmorillonite layers to improve the dispersibility of the montmorillonite, and the The modified montmorillonite is prepared by further loading zinc ions through electrostatic adsorption. The synergistic effect of octadecyltrimethoxysilane, cage-type silsesquioxane, montmorillonite and zinc oxide gives the coating excellent corrosion resistance and hydrophobicity. At the same time, zinc oxide has good light resistance and heat resistance. It forms a coordination compound with the carboxylate ions in the coating, thereby reducing the water sensitivity of the coating and improving the weather resistance of the coating. Then, the one-dimensional tubular modified carbon nanotubes and the two-dimensional layered modified montmorillonite are self-assembled to form a composite nanomaterial. The ammonium salt cations on the surface of the modified carbon nanotubes react with the Mg in the modified montmorillonite. 2+ , Ca 2+ The modified montmorillonite and the modified carbon nanotubes are then combined in the form of ionic bonds, which have a synergistic strengthening and toughening effect and enhance the resistance to chloride ion penetration.

[0033] The invention utilizes phenylphosphonic acid dichloride to react with meta-xylene to prepare a flame retardant (2,4-xylyl)phenylphosphine oxide, and then reacts the flame retardant (2,4-xylyl)phenylphosphine oxide with 1,5-naphthalenediamine and terephthalaldehyde, wherein the 1,5-naphthalenediamine has good thermal stability and can release smoke and flame retardant gas that inhibit combustion at high temperature, reacts an amino group at one end of the 1,5-naphthalenediamine structure with an aldehyde group at both ends of terephthalaldehyde to generate an N=C bond, and then utilizes a PH bond in the flame retardant (2,4-xylyl)phenylphosphine oxide structure to react with an N=C bond to obtain a modified curing agent, which is added into an anticorrosive coating to impart the coating with excellent flame retardant performance. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The carboxylated carbon nanotubes in the embodiments and comparative examples of the present invention have a diameter of 20 to 40 nm and a length of 30 μm, and are purchased from Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences; montmorillonite is purchased from Zhejiang Fenghong New Materials Co., Ltd.; and the epoxy resin has a viscosity of 1200 to 1400 mPa·s at 25° C. and is purchased from Lianyungang Zhongfu Lianzhong Composite Materials Group Co., Ltd.

[0036] Embodiment 1 A method for preparing a composite nanomaterial comprises the following steps:

[0037] (1) 0.02 g of N, N-diisopropylcarbodiimide, 0.02 g of 1-hydroxybenzotriazole and 1 g of carboxylated carbon nanotubes were added to 100 mL of N, N-dimethylformamide and ultrasonically dispersed uniformly. Then, 0.5 g of triethylenetetramine was added and stirred for 24 h. After the reaction was completed, the product was filtered and washed, and ultrasonically dispersed in 100 mL of deionized water. 10 mL of 6 mol / L hydrochloric acid solution was added dropwise under stirring and stirred for 0.5 h to prepare modified carbon nanotubes;

[0038] (2) 3.6 g of γ-aminopropyltriethoxysilane and 4.7 g of succinic anhydride were dissolved in 100 mL of N,N-dimethylformamide and stirred at 80° C. for 4 h to form a mixed solution, 3 g of montmorillonite was ultrasonically dispersed in 100 mL of N,N-dimethylformamide, 15 mL of deionized water was added and mixed, and then added to the mixed solution and stirred for 4 h. After the reaction was completed, the solution was centrifuged, washed, and dried to prepare activated montmorillonite;

[0039] (3) 45 g of deionized water, 20 mL of propanol, 5 mL of acetonitrile and 1 mL of tetraethylammonium hydroxide were placed in a reactor, 110.5 g of γ-aminopropyltriethoxysilane was added, and the mixture was stirred at 50 ° C for 24 h. After the reaction was completed, the mixture was subjected to rotary evaporation, washing and drying to prepare a cage-type silsesquioxane;

[0040] (4) 3 g of activated montmorillonite was ultrasonically dispersed in 40 mL of anhydrous ethanol, 3 mL of tetraethyl silicate and 2 mL of octadecyltrimethoxysilane were added, and the mixture was stirred at 50 ° C for 10 h. Then, the mixture was heated to 175 ° C, 15.4 g of cage-type silsesquioxane and 0.17 g of polyformaldehyde were added, and the mixture was stirred for 16 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain functionalized montmorillonite.

[0041] (5) 7 g of functionalized montmorillonite was ultrasonically dispersed in 200 mL of deionized water, and then 10.8 g of zinc nitrate was added and stirred at 65 ° C for 4 h. After the reaction was completed, the modified montmorillonite was prepared by centrifugation, washing, and drying;

[0042] (6) 10.2 g of modified montmorillonite was ultrasonically dispersed in 200 mL of deionized water, stirred at 80 °C for 25 min, and then 1 g of modified carbon nanotubes was added and stirred for 24 h. After the reaction was completed, the composite nanomaterial was prepared by filtration, washing, and drying.

[0043] Embodiment 2 A method for preparing a modified curing agent comprises the following steps:

[0044] A. Take 8g of phenyl phosphorus dichloride in a reactor, add 4.6g of m-xylene and 5.3g of anhydrous aluminum chloride, heat to 75°C for reaction for 10h, cool to room temperature after the reaction is completed, add 20mL of 10wt% hydrochloric acid and 40mL of benzene for hydrolysis, separate the organic layer, extract the water layer with 40mL of benzene, combine the organic layers, wash with deionized water, and remove the organic solvent under reduced pressure to prepare (2,4-xylyl)phenyl phosphorus oxide flame retardant;

[0045] B. Take 9.2g of 1,5-naphthalenediamine in a reactor, add 50mL of ethanol solvent to disperse evenly, take 4g of terephthalaldehyde, dissolve it in 50mL of ethanol and add it to the reactor, place it at 60°C for reflux reaction for 5h, then take 13.6g of (2,4-xylyl)phenylphosphine oxide flame retardant, dissolve it in 100mL of ethanol and add it to the reactor, heat it to 80°C for reaction for 7h, and after the reaction is completed, filter, wash and dry it to prepare a modified curing agent.

[0046] Example 3 A high-strength, corrosion-resistant marine aluminum alloy plate comprises an aluminum alloy substrate and an anti-corrosion coating coated on the surface of the aluminum alloy substrate, wherein the aluminum alloy substrate is composed of the following raw materials in weight percentage: Si: 0.4%, Fe: 0.5%, Cu: 0.2%, Mn: 0.1%, Mg: 0.85%, Cr: 0.04%, Zn: 0.15%, Ti: 0.05%, and the balance is Al and unavoidable impurities; the anti-corrosion coating comprises the following raw materials in weight parts: 41 parts of epoxy resin, 5 parts of the composite nanomaterial prepared in Example 1, 3 parts of the modified curing agent prepared in Example 2, 1 part of curing agent polyamide, 1 part of wetting agent polydimethylsiloxane, 0.5 parts of defoaming agent fatty alcohol polyoxyethylene ether, 0.2 parts of leveling agent sodium polyacrylate, and 0.1 parts of dispersant BYK-190.

[0047] The processing technology of the above-mentioned high-strength corrosion-resistant marine aluminum alloy plate comprises the following steps:

[0048] S1. Weigh each element according to the weight percentage and put it into a smelting furnace. Set the temperature in the furnace to 780°C. After all the materials in the furnace are melted, stir them evenly for 30 minutes. After stirring, heat them to 850°C and keep them still for 20 minutes. Slag is removed and samples are taken for analysis. The alloy composition is tested and adjusted to obtain alloy materials.

[0049] S2, refining the alloy material, the refining temperature is set to 720°C, the refining time is 20min, and after refining, it is left to stand for 20min, and then cast to obtain a slab, and then heat-treated at 175°C for 8h to obtain an aluminum alloy slab;

[0050] S3, hot rolling the aluminum alloy slab, heating it from 185°C to 260°C, then keeping it warm for 5h, and then cold rolling it, with the feed temperature of 320°C and the final rolling temperature of 230°C, cleaning and drying the slab after hot rolling and cold rolling to obtain an aluminum alloy substrate;

[0051] S4, taking parts by weight of epoxy resin, modified curing agent, composite nanomaterial, curing agent, wetting agent, defoaming agent, leveling agent and dispersant into a high-speed disperser for stirring and dispersing, heating to 145°C and evenly dispersing for 35 minutes, taking out the obtained anti-corrosion coating, and then evenly coating the anti-corrosion coating on the surface of the aluminum alloy substrate, drying and cooling, to obtain an anti-corrosion aluminum alloy plate;

[0052] S5. Soak the anti-corrosion aluminum alloy plate in hydrogen peroxide in a deep freezer for 15 minutes. Take it out and keep it at -10℃ for 20 minutes, then keep it at -40℃ for 15 minutes, then keep it at -90℃ for 40 minutes, take it out of the deep freezer, place it in the air to naturally return to room temperature, and place it for 2 hours to obtain a high-strength and corrosion-resistant marine aluminum alloy plate.

[0053] Example 4 A high-strength, corrosion-resistant marine aluminum alloy plate comprises an aluminum alloy substrate and an anti-corrosion coating coated on the surface of the aluminum alloy substrate, wherein the aluminum alloy substrate is composed of the following raw materials in weight percentage: Si: 0.7%, Fe: 0.6%, Cu: 0.35%, Mn: 0.12%, Mg: 0.98%, Cr: 0.22%, Zn: 0.2%, Ti: 0.1%, and the balance is Al and unavoidable impurities; the anti-corrosion coating comprises the following raw materials in weight parts: 52 parts of epoxy resin, 10 parts of the composite nanomaterial prepared in Example 1, 5 parts of the modified curing agent prepared in Example 2, 3 parts of curing agent polyamide, 2 parts of wetting agent polydimethylsiloxane, 0.7 parts of defoaming agent alkylphenol polyoxyethylene ether, 0.5 parts of leveling agent sodium polyacrylate, and 0.3 parts of dispersant BYK-191.

[0054] The processing technology of the above-mentioned high-strength and corrosion-resistant marine aluminum alloy plate is the same as that of Example 3.

[0055] Example 5 A high-strength, corrosion-resistant marine aluminum alloy plate comprises an aluminum alloy substrate and an anti-corrosion coating coated on the surface of the aluminum alloy substrate, wherein the aluminum alloy substrate is composed of the following raw materials in weight percentage: Si: 0.8%, Fe: 0.7%, Cu: 0.4%, Mn: 0.14%, Mg: 1.2%, Cr: 0.33%, Zn: 0.22%, Ti: 0.14%, and the balance is Al and unavoidable impurities; the anti-corrosion coating comprises the following raw materials in weight parts: 62 parts of epoxy resin, 15 parts of the composite nanomaterial prepared in Example 1, 7 parts of the modified curing agent prepared in Example 2, 5 parts of the curing agent polyamide, 3 parts of the wetting agent polydimethylsiloxane, 1 part of the defoaming agent alkylphenol polyoxyethylene ether, 1 part of the leveling agent sodium polyacrylate, and 0.5 parts of the dispersant BYK-191.

[0056] The processing technology of the above-mentioned high-strength and corrosion-resistant marine aluminum alloy plate is the same as that of Example 3.

[0057] Comparative Example 1 A method for preparing a composite nanomaterial comprises the following steps:

[0058] (1) 0.02 g of N, N-diisopropylcarbodiimide, 0.02 g of 1-hydroxybenzotriazole and 1 g of carboxylated carbon nanotubes were added to 100 mL of N, N-dimethylformamide and ultrasonically dispersed uniformly. Then, 0.5 g of triethylenetetramine was added and stirred for 24 h. After the reaction was completed, the product was filtered and washed, and ultrasonically dispersed in 100 mL of deionized water. 10 mL of 6 mol / L hydrochloric acid solution was added dropwise under stirring and stirred for 0.5 h to prepare modified carbon nanotubes;

[0059] (2) 10.2 g of montmorillonite was ultrasonically dispersed in 200 mL of deionized water, stirred at 80° C. for 25 min, and then 1 g of modified carbon nanotubes was added and stirred for 24 h. After the reaction was completed, the composite nanomaterial was prepared by filtering, washing, and drying.

[0060] Comparative Example 2 A method for preparing a composite nanomaterial comprises the following steps:

[0061] (1) 0.02 g of N, N-diisopropylcarbodiimide, 0.02 g of 1-hydroxybenzotriazole and 1 g of carboxylated carbon nanotubes were added to 100 mL of N, N-dimethylformamide and ultrasonically dispersed uniformly. Then, 0.5 g of triethylenetetramine was added and stirred for 24 h. After the reaction was completed, the product was filtered and washed, and ultrasonically dispersed in 100 mL of deionized water. 10 mL of 6 mol / L hydrochloric acid solution was added dropwise under stirring and stirred for 0.5 h to prepare modified carbon nanotubes;

[0062] (2) 3.6 g of γ-aminopropyltriethoxysilane and 4.7 g of succinic anhydride were dissolved in 100 mL of N,N-dimethylformamide and stirred at 80° C. for 4 h to form a mixed solution, 3 g of montmorillonite was ultrasonically dispersed in 100 mL of N,N-dimethylformamide, 15 mL of deionized water was added and mixed, and then added to the mixed solution and stirred for 4 h. After the reaction was completed, the solution was centrifuged, washed, and dried to prepare activated montmorillonite;

[0063] (3) 45 g of deionized water, 20 mL of propanol, 5 mL of acetonitrile and 1 mL of tetraethylammonium hydroxide were placed in a reactor, 110.5 g of γ-aminopropyltriethoxysilane was added, and the mixture was stirred at 50 ° C for 24 h. After the reaction was completed, the mixture was subjected to rotary evaporation, washing and drying to prepare a cage-type silsesquioxane;

[0064] (4) 3 g of activated montmorillonite was ultrasonically dispersed in 40 mL of anhydrous ethanol, 3 mL of tetraethyl silicate and 2 mL of octadecyltrimethoxysilane were added, and the mixture was stirred at 50 ° C for 10 h. Then, the mixture was heated to 175 ° C, 15.4 g of cage-type silsesquioxane and 0.17 g of polyformaldehyde were added, and the mixture was stirred for 16 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain functionalized montmorillonite.

[0065] (5) 10.2 g of functionalized montmorillonite was ultrasonically dispersed in 200 mL of deionized water, stirred at 80 °C for 25 min, and then 1 g of modified carbon nanotubes was added and continued to stir for 24 h. After the reaction was completed, the composite nanomaterial was prepared by filtering, washing, and drying.

[0066] Comparative Example 3 A high-strength, corrosion-resistant marine aluminum alloy plate, wherein an equal amount of the composite nanomaterial prepared in Example 1 and added to the anti-corrosion coating in Example 5 is replaced by the composite nanomaterial prepared in Comparative Example 1, and the remaining components are the same as in Example 5.

[0067] The processing technology of the above-mentioned high-strength and corrosion-resistant marine aluminum alloy plate is the same as that of Example 3.

[0068] Comparative Example 4 is a high-strength, corrosion-resistant marine aluminum alloy plate, in which an equal amount of the composite nanomaterial prepared in Example 1 and added to the anti-corrosion coating in Example 5 is replaced by the composite nanomaterial prepared in Comparative Example 2, and the remaining components are the same as in Example 5.

[0069] The processing technology of the above-mentioned high-strength and corrosion-resistant marine aluminum alloy plate is the same as that of Example 3.

[0070] Comparative Example 5 is a high-strength, corrosion-resistant marine aluminum alloy plate, in which an equal amount of the modified curing agent prepared in Example 2 added to the anti-corrosion coating of Example 5 is replaced by a curing agent polyamide, and the remaining components are the same as in Example 5.

[0071] The processing technology of the above-mentioned high-strength and corrosion-resistant marine aluminum alloy plate is the same as that of Example 3.

[0072] Performance Testing

[0073] The high-strength corrosion-resistant marine aluminum alloy plates prepared in Examples 3-5 and Comparative Examples 3-5 were subjected to performance tests: referring to GB / T 16865-2013, the aluminum alloy plates were processed into standard tensile specimens, and were stretched at room temperature on a DNS200 electronic tensile testing machine at a stretching rate of 2 mm / min to perform a tensile mechanical property test; a contact angle measuring instrument was used to test the water contact angle of the coating; an "×" treatment was drawn on the surface of the aluminum alloy, and then the aluminum alloy was placed in a salt spray test chamber for a salt spray aging test, with a 5% NaCl solution as the spray medium, the test temperature was maintained at (35±2)°C, the pH value was about 6.7-7.5, and a continuous spray method was used to test the salt spray resistance of the coating; referring to GB / T 1843-2008, an cantilever beam impact strength tester was used to test the impact resistance of the aluminum alloy coating; the flame retardant performance was tested by the limiting oxygen index, and the data results are shown in Table 1.

[0074] Table 1 Test results of sample performance

[0075]

[0076] From the data in Table 1, it can be seen that the aluminum alloy sheets prepared in Examples 3-5 of the present invention have excellent strength, elongation, impact resistance, corrosion resistance and flame retardancy. The water contact angle, impact resistance and corrosion potential measured in Comparative Example 3 are lower than those in Examples 3-5, and bubbles and corrosion products appear on the coating surface, indicating that the activated montmorillonite is functionalized with octadecyltrimethoxysilane and cage-type silsesquioxane, and loaded with zinc ions can improve the corrosion resistance and impact strength of the aluminum alloy coating. In Comparative Example 4, bubbles appear on the coating surface, and the corrosion potential is reduced to -0.19, indicating that the loading of zinc ions can further improve the corrosion resistance of the aluminum alloy coating. In Comparative Example 5, the limiting oxygen index is significantly lower than that in Examples 3-5, because no modified curing agent containing flame retardancy is added.

[0077] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0078] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A high-strength, corrosion-resistant marine aluminum alloy plate, characterized in that: It includes an aluminum alloy substrate and an anti-corrosion coating coated on the surface of the aluminum alloy substrate, wherein the aluminum alloy substrate is composed of the following raw materials in weight percentage: Composition: Si: 0.4-0.8%, Fe: 0.5-0.7%, Cu: 0.15-0.4%, Mn: 0.1-0.15%, Mg: 0.8-1.2%, Cr: 0.04-0.35%, Zn: 0.1-0.25%, Ti: 0.05-0.15%, the balance is Al and inevitable impurities; the anti-corrosion coating comprises the following raw materials in parts by weight: 40-65 parts of epoxy resin, 5-15 parts of composite nanomaterials, 3-7 parts of modified curing agent, 1-5 parts of curing agent, 1-3 parts of wetting agent, 0.5-1 part of defoaming agent, 0.1-1 part of leveling agent, 0.1-0.5 part of dispersant; The composite nano material is prepared by functionalizing activated montmorillonite with octadecyltrimethoxysilane and cage-type silsesquioxane, further loading zinc ions through electrostatic adsorption, and then self-assembling with modified carbon nanotubes to form the composite nano material, wherein the activated montmorillonite is prepared by treating with γ-aminopropyltriethoxysilane and succinic anhydride, and the modified carbon nanotubes are prepared by amidation reaction of carboxylated carbon nanotubes with triethylenetetramine and proton acid salt formation reaction; and the modified curing agent is prepared by reacting a flame retardant (2,4-xylyl)phenylphosphine oxide with 1,5-naphthalenediamine and terephthalaldehyde through a chemical reaction.

2. The high-strength, corrosion-resistant marine aluminum alloy sheet according to claim 1, characterized in that: The curing agent is polyamide; the wetting agent is polydimethylsiloxane; the defoaming agent is one of fatty alcohol polyoxyethylene ether or alkylphenol polyoxyethylene ether; the leveling agent is sodium polyacrylate; and the dispersant is one of BYK-190 or BYK-191.

3. The high-strength, corrosion-resistant marine aluminum alloy sheet according to claim 1, characterized in that: The preparation method of the composite nanomaterial comprises the following steps: (1) N, N-diisopropylcarbodiimide, 1-hydroxybenzotriazole and carboxylated carbon nanotubes are added to N, N-dimethylformamide, and ultrasonically dispersed uniformly. Then, triethylenetetramine is added and stirred for 20 to 24 hours. After the reaction is completed, the product is filtered and washed, and ultrasonically dispersed in deionized water. Hydrochloric acid solution is added dropwise under stirring and stirred for 0.5 to 1 hour to prepare modified carbon nanotubes; (2) taking γ-aminopropyltriethoxysilane and succinic anhydride in N,N-dimethylformamide, stirring at 75-90° C. for 2-4 hours to form a mixed solution, ultrasonically dispersing montmorillonite in N,N-dimethylformamide, adding deionized water to mix, and then adding it to the mixed solution and continuing to stir for 3-5 hours. After the reaction is completed, centrifuging, washing, and drying are performed to prepare activated montmorillonite; (3) Deionized water, propanol, acetonitrile and tetraethylammonium hydroxide are placed in a reactor, γ-aminopropyltriethoxysilane is added, and the mixture is stirred at 45 to 55° C. for 20 to 24 hours. After the reaction is completed, the mixture is subjected to rotary evaporation, washing and drying to prepare a cage-type silsesquioxane; (4) taking activated montmorillonite and dispersing it in anhydrous ethanol by ultrasonic, adding tetraethyl silicate and octadecyltrimethoxysilane, stirring and reacting at 45-60° C. for 8-12 hours, then heating to 170-180° C., adding cage-type silsesquioxane and polyformaldehyde, and continuing to stir and react for 14-16 hours. After the reaction is completed, centrifugation, washing, and drying are performed to prepare functionalized montmorillonite; (5) ultrasonically dispersing the functionalized montmorillonite in deionized water, then adding zinc nitrate and stirring the mixture at 55-70° C. for 3-4 hours. After the reaction is completed, the mixture is centrifuged, washed, and dried to obtain a modified montmorillonite. (6) The modified montmorillonite is ultrasonically dispersed in deionized water, stirred at 75-85° C. for 15-30 min, and then the modified carbon nanotubes are added and stirred for 20-24 h. After the reaction is completed, the composite nanomaterial is prepared by filtering, washing, and drying.

4. The high-strength, corrosion-resistant marine aluminum alloy sheet according to claim 3, characterized in that: In the step (4), the addition ratio of activated montmorillonite, tetraethyl silicate, octadecyltrimethoxysilane and cage-type silsesquioxane is 3 g: 2-3 mL: 1-2 mL: 10-16 g.

5. The high-strength, corrosion-resistant marine aluminum alloy sheet according to claim 3, characterized in that: In the step (5), the mass ratio of the functionalized montmorillonite to zinc nitrate is 1:1.5-2.

6. The high-strength, corrosion-resistant marine aluminum alloy sheet according to claim 3, characterized in that: In the step (6), the mass ratio of the modified montmorillonite to the modified carbon nanotubes is 10-15:

1.

7. The high-strength, corrosion-resistant marine aluminum alloy sheet according to claim 1, characterized in that: The preparation method of the modified curing agent comprises the following steps: A. Phenyl phosphorus dichloride is placed in a reactor, m-xylene and anhydrous aluminum chloride are added, the temperature is raised to 70-85° C. for reaction for 8-12 hours, after the reaction is completed, the reaction is cooled to room temperature, hydrochloric acid and benzene are added for hydrolysis, the organic layer is separated, the aqueous layer is extracted with benzene, the organic layers are combined, washed with deionized water, and the organic solvent is evaporated under reduced pressure to prepare (2,4-xylyl)phenyl phosphorus oxide flame retardant; B. Take 1,5-naphthalenediamine in a reactor, add ethanol solvent to disperse it evenly, take terephthalaldehyde dissolved in ethanol and add it to the reactor, place it at 50-75°C for reflux reaction for 4-6 hours, then take (2,4-xylyl)phenylphosphine oxide flame retardant dissolved in ethanol and add it to the reactor, heat it to 75-85°C for reaction for 5-7 hours, and after the reaction is completed, filter, wash and dry it to prepare a modified curing agent.

8. The high-strength, corrosion-resistant marine aluminum alloy sheet according to claim 7, characterized in that: In the step A, the mass ratio of phenylphosphonium dichloride, m-xylene and anhydrous aluminum chloride is 1:0.5-0.7:0.5-0.

8.

9. The high-strength, corrosion-resistant marine aluminum alloy plate according to claim 7, characterized in that: In the step B, the mass ratio of 1,5-naphthalenediamine, terephthalaldehyde and (2,4-xylyl)phenylphosphine oxide flame retardant is 2.3-2.7:1:3.4-4.

1.

10. A processing technology for a high-strength, corrosion-resistant marine aluminum alloy plate as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh each element according to the weight percentage and put it into a smelting furnace. Set the temperature in the furnace to 750-800°C. After all the materials in the furnace are melted, stir them evenly for 30-45 minutes. After stirring, heat them to 850°C and keep them still for 10-20 minutes. Slag is removed and samples are taken for analysis. The alloy composition is tested and adjusted to obtain alloy materials. S2, refining the alloy material, the refining temperature is set to 700-730°C, the refining time is 20-25min, and after refining, it is left to stand for 15-20min, and then cast to obtain a slab, and then heat-treat it at 150-180°C for 4-8h to obtain an aluminum alloy slab; S3, hot rolling the aluminum alloy slab, heating it from 180 to 220° C. to 250 to 280° C., then keeping it warm for 5 to 7 hours, and then cold rolling it, with a feed temperature of 300 to 350° C. and a final rolling temperature of 220 to 250° C., cleaning and drying the slab after hot rolling and cold rolling to obtain an aluminum alloy substrate; S4, taking parts by weight of epoxy resin, modified curing agent, composite nanomaterial, curing agent, wetting agent, defoaming agent, leveling agent and dispersant into a high-speed disperser for stirring and dispersing, heating to 120-150° C. and evenly dispersing for 30-50 minutes, taking out the obtained anti-corrosion coating, and then evenly coating the anti-corrosion coating on the surface of the aluminum alloy substrate, drying and cooling, to obtain an anti-corrosion aluminum alloy plate; S5. Soak the anti-corrosion aluminum alloy plate in hydrogen peroxide in a deep freezer for 10 to 20 minutes. Take it out and keep it at -10°C for 20 to 30 minutes, then keep it at -40°C for 10 to 20 minutes, then keep it at -90°C for 30 to 40 minutes, then take it out of the deep freezer, place it in the air to naturally return to room temperature, and place it for 1 to 2 hours to obtain a high-strength and corrosion-resistant marine aluminum alloy plate.

Citation Information

Patent Citations

  • Method of coating a component

    CA2620696A1

  • TPO waterproof coiled material comprising nanometer flame retardant and preparation method for TPO waterproof coiled material

    CN104356459A

  • High-toughness spraying-free polyamide 6 material and preparation method thereof

    CN110551390A

  • Nano-cage flame retardant modified epoxy resin floor paint and preparation method thereof

    CN113174187A

  • Waterborne epoxy resin anticorrosive paint and preparation method thereof

    CN115216170A

Cited By

  • Environment-friendly fluorine-free aluminum alloy surface anticorrosive paint and preparation method thereof

    CN120718517A

  • Environment-friendly fluorine-free anticorrosive coating for aluminum alloy surface and preparation method thereof

    CN120718517B

  • High-strength cast aluminum alloy material for 5G case and preparation method of high-strength cast aluminum alloy material

    CN120989431A